Role of Work Engagement, Autonomy Support, Psychological Capital, and Economic Factors to Educator and Staff Well-being in the Philippines - Justin Vianey M. Embalsado; Beatriz C. Balilu; Mary Anne Joseph T. Montoya; Rachelle Louse C. Chavez; Olga Angelinetta P. Tulabut; Roger S. Mangalus; Cherry Lou M. De Ala; Abigail B. Gonzales; June R. De Leon (Psychocentrum Review, 2023)
Educational institutions are transitioning their learning modalities to flexible learning from remote education; educators and staff continuously encounter ambiguous work demands that negatively affect their well-being. Literature indicates the influence of autonomy support, psychological capital, work engagement, and economic factors (i.e., financial preparedness and job insecurity) on well-being. We propose that social, psychological, work, and economic factors influence the well-being of university educators and staff. 315 employees voluntarily completed the autonomy support, work engagement, hope, self-efficacy, job insecurity, and financial preparedness scales. We used IBM SPSS Amos for the confirmatory factor analysis and structural equation modeling. Five separate models were conducted to test the research objective. Results indicate good to excellent model fit indices for the research scales and structural model. We also found that self-efficacy, work engagement, hope, and financial preparedness during emergencies positively predict well-being, while job insecurity is detrimental. Our findings could serve as a basis for mental health programs to address the mental issues of educators and staff.